THERAPEUTIC POTENTIAL OF OZONE AND L-CARNITINE COMBINED ADMINISTRATIONS AGAINST EXPERIMENTALLY-INDUCED ACETAMINOPHEN - E. Paldir; H. A. Eroglu 2 (Journal of Animal and Plant Sciences, 2020)
Acetaminophen is a widely used medicine with antipyretic and analgesic effects. N-acetyl-P-benzoquinoneimine accumulation after a high-dose of acetaminophen leads to hepatotoxicity, depletion of glutathione stores, and suppression of the antioxidant defense mechanism. As a result, N-acetyl-P-benzoquinoneimine cannot be eliminated from the body and hepatotoxicity occurs. In this study, the effects of the separate and combined use of ozone and L-carnitine in high-dose acetaminophen induced hepatotoxicity was investigated. A total of 56 female Wistar albino rats were randomly divided into 8 groups of seven rats. Acetaminophen was administered orally as a single dose to induce liver damage, and 0.5 mg/kg of 95% oxygen plus 5% ozone gas mixture was administered intraperitoneally. After 1-hour APAP administration, L-carnitine were given 500 mg/kg by intraperitoneally. Serum and tissue oxidant/antioxidant parameters were measured to deduce their combined effect. ANOVA and Tukey’s multiple comparison test were used for statistical analysis. Acetaminophen+L-carnitine+ozone administration caused a significant decrease in the levels of serum malondialdehyde, total oxidant level, aspartate aminotransferase, alanine aminotransferase, and tissue malondialdehyde, total oxidant status levels, while it led to a significant increase in the levels of tissue and serum total antioxidant levels. Nonetheless, a clear evidence of superiority over the sole use of ozone or L-carnitine in acetaminophen induced hepatotoxicity was not present. It was concluded that ozone, L-carnitine and ozone+L-carnitine treatments in acetaminophen induced hepatotoxicity protected the organism against the harmful effects of free radicals and activated the antioxidant mechanism by suppressing oxidative stress.
Keywords: Acetaminophen; Hepatotoxicity; L-carnitine; Liver; ozone